Impact of BMI z-score on left ventricular mechanics in adolescent girls - Paysal, Justine; Merlin, Etienne; Rochette, Emmanuelle; Terral, Daniel; Nottin, Stéphane (Frontiers in Pediatrics, 2023)
Background: Adolescent weight disorders ranging from anorexia nervosa (AN) to obesity (OB) can impact the heart by causing opposite alterations in its morphology, suggesting a direct impact of body mass index (BMI) on the heart. Cardiac function is relatively preserved as assessed by standard echocardiography. However, few studies have used 2D speckle-tracking echocardiography (2D-STE), which can detect subtle alterations of left ventricular (LV) function by evaluating deformations. The aim of this study was to assess the link between BMI z-score of female adolescents and myocardial function.Methods: Ninety-one female adolescents comprising 26 AN patient (age 14.6 ± 1.9 y), 28 OB patients (age 13.2 ± 1.4 y), and 37 controls (age 14.0 ± 2.0 y) underwent 2D-STE to assess LV morphology and myocardial global and regional deformations.The BMI z-score of our population ranged from −4.6 to 5.2. LV morphological remodeling was significantly and positively correlated with BMI z-score (R² = 0.456, p < 0.0001 for LV mass). Global longitudinal strain (LS) and regional LS recorded at the mid and apical levels were significantly correlated with BMI z-score (R² = 0.196, p = 0.0001 and R² = 0.274, p < 0.0001 respectively for apical and medial LS). Circumferential strains and twisting mechanics were not correlated with BMI z-score. Fibrinogen and systolic blood pressure were the main variables explaining the alteration of longitudinal strainsLS.We observed that BMI z-score had an impact on LV mechanics especially on medial and apical LS. Neither circumferential nor twisting mechanics were altered by BMI zscore in female adolescents.